Alih Kode Dan Campur Kode Dalam Podcast Catatan Najwa Bersama Maudy Ayunda - Aghist Muflihah Zahra; Mitha Anggraeni; Ian Wahyuni (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
In recent years, podcast content on YouTube social media has been in great demand by the wider community. Especially one of the podcasts from Najwa Shihab's YouTube channel which is the object of this research. Object selection is based on the story used by Najwa Shihab and the guest star on the podcast, Maudy Ayunda. Throughout the video, they use Indonesian as well as English. In addition, both of them also insert elements of words in English. This study aims to describe: (1) Types of code-switching and code-mixing in the Nada Najwa podcast with Maudy Ayunda (2) Factors that cause code-switching and code-mixing in the podcast. This research is a descriptive qualitative research. The results of the analysis of this study indicate that there is a type of code switching with Indonesian to English speech and vice versa, namely English to Indonesian. In addition, it was found the insertion of English elements in the speech between the presenter and the speaker.